Multi-element wear-resistant and temperature-resistant protective coating material for gas turbine and preparation method thereof
By introducing the VCoNiMo medium-entropy alloy of FCC+σ phase into the coating, and precipitating the L12 co-glass nanophase and α-MoO3 phase through supersonic particle bombardment and heat treatment, the problem of insufficient wear and temperature resistance of the existing coating materials is solved, and the wear and temperature resistance of the coating is significantly improved.
Patent Information
- Application Number
- CN202411882727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
AI Technical Summary
The existing gas turbine coating materials are still insufficient in terms of wear and temperature resistance, and it is difficult to meet the service requirements of gas turbine components under harsh working conditions.
The VCoNiMo mid-entropy alloy of FCC+σ phase was introduced into the bonded phase, and the surface treatment and heat treatment of supersonic particles were bombarded with supersonic particles to precipitate the L12 co-glass nanophase and α-MoO3 phase to improve the wear resistance and temperature resistance of the coating.
Through the medium entropy alloy and the precipitated reinforced phase, the wear resistance and temperature resistance of the coating are significantly improved, meeting the requirements of gas turbine components under harsh working conditions.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The present invention relates to a protective coating material and a preparation method thereof, and in particular to a multi-element wear-resistant and temperature-resistant protective coating material for a gas turbine and a preparation method thereof, and belongs to the field of high-end equipment manufacturing and new materials. Background Art
[0002] At present, the working efficiency of gas turbines is constantly improving. The service conditions of various important components in the operation of gas turbines are very harsh, and the requirements for wear resistance and temperature resistance are getting higher and higher. The alloy matrix material can hardly meet the service requirements, and surface coating treatment is usually required to meet the requirements of harsh working conditions.
[0003] CN109575650A discloses a thermal spraying anti-wear coating suitable for metal substrates and its preparation process. The coating is composed of Cr3C2, TiB2, Fe3B, Ni and ceramic powder, and its ingredient percentage is Cr3C2 19%-21%; TiB2 7%-9%; Fe3B 15%-20%; Ni 0.5%-1%; ceramic powder 50%-60%. The coating is composed of Cr3C2, TiB2, Fe3B, Ni and ceramic powder, and its ingredient percentage is Cr3C2 20%; TiB2 8%; Fe3B 15; Ni 0.5%; ceramic powder 56.5%. The invention has the properties of anti-wear, high temperature corrosion resistance and oxidation resistance. CN117418229A discloses a wear-resistant protective composite coating and its application. The present invention utilizes supersonic flame spraying technology to spray Cr3C2-NiCr coating, which gathers the advantages of Cr3C2-NiCr material and supersonic spraying, forming a new material with the advantages of high temperature resistance, oxidation resistance, corrosion resistance, high temperature wear resistance and high temperature erosion resistance, low porosity, etc.; and then utilizes arc ion plating to prepare TaC coating, with NiCr as the base layer and Ti as the transition layer, which has the characteristics of low deposition temperature, simple operation, and strong applicability, and can improve the bonding performance between Cr3C2-NiCr layer and TaC coating with different compositions. However, the wear resistance and temperature resistance of existing coating materials are still insufficient, and it is very necessary to develop high-performance coating materials and their preparation technology. Summary of the invention
[0004] The purpose of the present invention is to provide a multi-element wear-resistant and heat-resistant protective coating material for a gas turbine and a preparation method thereof. The present invention proposes to introduce a VCoNiMo medium entropy alloy of FCC+σ phase into the bonding phase, and after surface treatment and heat treatment by supersonic particle bombardment, L12 coherent nanophase and α-MoO3 phase are precipitated on the surface of the coating, and the α-MoO3 phase can reduce the friction coefficient, and the precipitated chemical short-range ordered coherent nanophase is used to strengthen the coating, and improve the wear resistance and temperature resistance.
[0005] The multi-element wear-resistant and temperature-resistant protective coating material for a gas turbine of the present invention is characterized in that its composition is that the medium-entropy alloy powder containing Mo accounts for 20-30% by weight, and the rest is Cr3C2 powder; the molar ratio of Mo, Ni, Co and V in the medium-entropy alloy containing Mo is (1-2):10:10:10; the coating phase composition is Cr3C2+Ni+VCoNiMo with FCC structure+σ phase with tetragonal topological structure+α-MoO3 with orthorhombic structure, the coating thickness is 200-300μm, and its surface layer has a deformation layer with a thickness of 20-35μm, and a 5-15nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer.
[0006] The method for preparing the multi-element wear-resistant and temperature-resistant protective coating for a gas turbine of the present invention is characterized by comprising the following steps in sequence: (1) Preparation of Mo-containing medium-entropy alloy powder: Mo, Ni, Co, and V powders were weighed in a molar ratio of (1-2):10:10:10, and the mixture was stirred and ball-milled for 72-120 h. After filtering and drying, a Mo-containing medium-entropy alloy powder with a particle size of 1.0-1.5 μm was prepared; (2) Preparation of multi-element wear-resistant and heat-resistant protective coating powder: Weigh the raw material powder according to weight percentage, of which the Mo-containing medium-entropy alloy powder accounts for 20-30%, and the rest is Cr3C2 powder; the weighed raw material powder is subjected to planetary ball milling for 10-15 hours, filtered and spray-dried, and then vacuum sintered at 1150-1250℃ for 1-2 hours to prepare the multi-element wear-resistant and heat-resistant protective coating powder; (3) Preparation of wear-resistant and heat-resistant coating by HVOF: The prepared protective coating powder is used as feed material, and the wear-resistant and heat-resistant coating is prepared by HVOF. During the thermal spraying process, part of the Mo element is oxidized to form α-MoO3 with a layered structure, and a σ phase rich in Mo and V is precipitated in the medium-entropy alloy matrix. The phase composition of the coating is Cr3C2+FCC structure VCoNiMo + tetragonal topological structure σ phase + orthorhombic structure α-MoO3 coating protective coating, the σ phase size is about 0.5~0.8μm, and the coating thickness is 200~300μm; (4) Surface treatment by supersonic particle bombardment: The protective coating surface was treated by supersonic particle bombardment using Al2O3 particles with an average particle size of 50 μm. The carrier gas was air with an air pressure of 1.0-1.5 MPa. After 2-5 min of bombardment, a 20-35 μm thick deformation layer was formed on the coating surface, of which 2×10 9 ~6×10 9 mm -2 High density of dislocations; (5) Precipitation of strengthening phase in wear-resistant and heat-resistant coating: The coating treated by supersonic particle bombardment is heated to 980~1100℃ in vacuum, kept at this temperature for 1~2h to complete solid solution, and then filled with argon for cooling; then heated to 800~850℃, kept at this temperature for 2~3h and then cooled in the furnace. A σ phase with a tetragonal topological structure of 0.1~0.3μm is precipitated in the VCoNiMo in the wear-resistant and heat-resistant coating, and a 5~15nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer on the coating surface.
[0007] The method for preparing the multi-element wear-resistant and temperature-resistant protective coating for a gas turbine of the present invention is further characterized in that: (1) When preparing the Mo-containing medium entropy alloy powder, the stirring ball milling speed is 700-800 r / min, WC-8Co grinding balls with a diameter of 6-10 mm are used, the ball milling medium is anhydrous ethanol, and the weight ratio of grinding balls: powder: anhydrous ethanol during ball milling is 30:2:3. After ball milling, it is filtered with a 400-mesh screen and dried at 90-100°C. (2) When preparing the multi-element wear-resistant and heat-resistant protective coating powder, the ball mill speed is 200~300r / min, WC-10Co grinding balls with a diameter of 10mm are used, the ball milling medium is anhydrous ethanol, PEG4000 is added as a molding agent, the weight ratio of grinding ball: powder: anhydrous ethanol: PEG2000 is 10:1:2:0.26, and a 400-mesh sieve is used for filtration after ball milling. During spray drying, the atomizing disk speed is 6500~7000r / min, and the drying temperature is 120~130℃; (3) When HVOF is used to prepare wear-resistant and temperature-resistant coatings, the oxygen flow rate is 800~900L / min, the kerosene flow rate is 23~27L / h, the spray distance is 300~320mm, the powder feeding rate is 60~70g / min, and the spray gun moving speed is 800~1000mm / s; (4) When the supersonic particles bombard the surface for treatment, the bombardment angle is 90° and the bombardment distance is 40~50mm; (5) When the strengthening phase precipitates in the wear-resistant and heat-resistant coating, the initial vacuum degree is 0.5~1Pa and the heating rate is 1~5℃ / min.
[0008] The advantages of the present invention are: (1) in the coating, the medium entropy alloy has better mechanical properties, wear resistance and temperature resistance than the traditional alloy. (2) the σ phase of the tetragonal topological structure and the L12 short-range ordered coherent nanophase are precipitated in the medium entropy alloy, which can strengthen the coating and improve its wear resistance; (2) the Mo element forms α-MoO3, which can reduce the friction coefficient and improve the wear resistance; (3) after the surface treatment by supersonic particle bombardment and subsequent treatment, the size of the σ phase is reduced and the strengthening effect of the second phase is enhanced. (4) the formation of the medium entropy alloy and the dual strengthening phase therein can improve the temperature resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 Schematic diagram of the preparation method of the multi-element wear-resistant and temperature-resistant protective coating for a gas turbine according to the present invention. DETAILED DESCRIPTION
[0010] Example 1: The composition of the multi-element wear-resistant and heat-resistant protective coating material for gas turbines is calculated by weight percentage, with Mo-containing medium-entropy alloy powder accounting for 22% and the rest being Cr3C2 powder; the molar ratio of Mo, Ni, Co and V in the Mo-containing medium-entropy alloy is 1:10:10:10; the coating phase composition is Cr3C2+Ni+VCoNiMo with FCC structure + σ phase with tetragonal topological structure + α-MoO3 with orthorhombic structure, the coating thickness is 210μm, and its surface has a 22μm thick deformation layer, in which a 6 nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer.
[0011] Preparation method of multi-element wear-resistant and temperature-resistant protective coating for gas turbine, such as Figure 1 As shown, the following steps are included in sequence: (1) Preparation of Mo-containing medium-entropy alloy powder: Mo, Ni, Co, and V powders were weighed in a molar ratio of 1:10:10:10, and stirred and ball-milled for 72 h at a stirring and ball-milling speed of 700 r / min. WC-8Co grinding balls with a diameter of 6 mm were used. The ball-milling medium was anhydrous ethanol. The weight ratio of grinding balls: powder: anhydrous ethanol during ball milling was 30:2:3. After ball milling, the mixture was filtered through a 400-mesh sieve and dried at 90°C to prepare a Mo-containing medium-entropy alloy powder with a particle size of 1.4 μm. (2) Preparation of multi-element wear-resistant and heat-resistant protective coating powder: Weigh the raw material powder according to the weight percentage, of which the Mo-containing medium-entropy alloy powder accounts for 22%, and the rest is Cr3C2 powder; the weighed raw material powder is subjected to planetary ball milling for 12 hours, the ball mill speed is 200r / min, WC-10Co grinding balls with a diameter of 10mm are used, the ball milling medium is anhydrous ethanol, PEG4000 is added as a molding agent, and the weight ratio of grinding balls: powder: anhydrous ethanol: PEG2000 is 10:1:2:0.26. After ball milling, filter with a 400-mesh sieve. During spray drying, the atomizing disk speed is 6500r / min, the drying temperature is 120℃, and then vacuum sintered at 1150℃ for 1h to prepare multi-element wear-resistant and heat-resistant protective coating powder; (3) Preparation of wear-resistant and heat-resistant coating by HVOF: The prepared protective coating powder was used as feed material, and the wear-resistant and heat-resistant coating was prepared by HVOF. The oxygen flow rate was 800L / min, the kerosene flow rate was 23L / h, the spray distance was 300mm, the powder feeding rate was 60g / min, and the spray gun moving speed was 8000mm / s. During the thermal spraying process, part of the Mo element was oxidized to form α-MoO3 with a layered structure, and a σ phase rich in Mo and V was precipitated in the medium entropy alloy matrix. The phase composition of the coating was Cr3C2+FCC structure VCoNiMo + tetragonal topological structure σ phase + orthorhombic structure α-MoO3 coating protective coating, the σ phase size was about 0.6μm, and the coating thickness was 210μm; (4) Surface treatment by supersonic particle bombardment: The protective coating surface was treated by supersonic particle bombardment using Al2O3 particles with an average particle size of 50 μm. The carrier gas was air, the air pressure was 1.1 MPa, the bombardment angle was 90°, and the bombardment distance was 42 mm. After 2 minutes of bombardment, a 22 μm thick deformation layer was formed on the coating surface, of which 2.7×10 9 mm -2 High density of dislocations; (5) Precipitation of strengthening phase in wear-resistant and heat-resistant coating: The coating treated with supersonic particle bombardment was heated to 980°C in vacuum, with an initial vacuum degree of 0.5 Pa and a heating rate of 1°C / min. It was kept at this temperature for 1 h to complete the solid solution, and then filled with argon for cooling; it was then heated to 800°C at a heating rate of 2°C / min. After keeping at this temperature for 2 h, it was cooled in the furnace. A σ phase with a tetragonal topological structure of 0.1 μm was precipitated in the VCoNiMo in the wear-resistant and heat-resistant coating, and a 6 nm L12 short-range ordered coherent nanophase was precipitated in the VCoNiMo phase in the deformation layer on the coating surface.
[0012] Example 2: The composition of the multi-element wear-resistant and heat-resistant protective coating material for gas turbines is calculated by weight percentage, with Mo-containing medium-entropy alloy powder accounting for 26% and the rest being Cr3C2 powder; the molar ratio of Mo, Ni, Co and V in the Mo-containing medium-entropy alloy is 1.7:10:10:10; the coating phase composition is Cr3C2+Ni+FCC structure VCoNiMo + tetragonal topological structure σ phase + orthorhombic structure α-MoO3, the coating thickness is 260μm, and its surface has a 32μm thick deformation layer, and a 12nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer.
[0013] Preparation method of multi-element wear-resistant and temperature-resistant protective coating for gas turbine, such as Figure 1 As shown, the following steps are included in sequence: (1) Preparation of Mo-containing medium-entropy alloy powder: Mo, Ni, Co, and V powders were weighed in a molar ratio of 1.7:10:10:10, and stirred and ball-milled for 100 h at a stirring and ball-milling speed of 800 r / min. WC-8Co grinding balls with a diameter of 8 mm were used. The ball-milling medium was anhydrous ethanol. The weight ratio of grinding balls: powder: anhydrous ethanol during ball milling was 30:2:3. After ball milling, the mixture was filtered through a 400-mesh sieve and dried at 100°C to prepare a Mo-containing medium-entropy alloy powder with a particle size of 1.2 μm. (2) Preparation of multi-element wear-resistant and heat-resistant protective coating powder: Weigh the raw material powder according to the weight percentage, of which the Mo-containing medium-entropy alloy powder accounts for 26%, and the rest is Cr3C2 powder; the weighed raw material powder is subjected to planetary ball milling for 14 hours, the ball mill speed is 280r / min, WC-10Co grinding balls with a diameter of 10mm are used, the ball milling medium is anhydrous ethanol, PEG4000 is added as a molding agent, and the weight ratio of grinding balls: powder: anhydrous ethanol: PEG2000 is 10:1:2:0.26. After ball milling, filter with a 400-mesh sieve. During spray drying, the atomizing disk speed is 7000r / min, the drying temperature is 125℃, and then vacuum sintered at 1250℃ for 1.5h to prepare multi-element wear-resistant and heat-resistant protective coating powder; (3) Preparation of wear-resistant and heat-resistant coating by HVOF: The prepared protective coating powder was used as feed material, and the wear-resistant and heat-resistant coating was prepared by HVOF. The oxygen flow rate was 900 L / min, the kerosene flow rate was 25 L / h, the spray distance was 310 mm, the powder feeding rate was 65 g / min, and the spray gun moving speed was 900 mm / s. During the thermal spraying process, part of the Mo element was oxidized to form α-MoO3 with a layered structure, and a σ phase rich in Mo and V was precipitated in the medium entropy alloy matrix. The phase composition of the coating was Cr3C2+FCC structure VCoNiMo + tetragonal topological structure σ phase + orthorhombic structure α-MoO3 coating protective coating, the σ phase size was about 0.7 μm, and the coating thickness was 260 μm; (4) Surface treatment by supersonic particle bombardment: The protective coating surface was treated by supersonic particle bombardment using Al2O3 particles with an average particle size of 50 μm. The carrier gas was air, the air pressure was 1.04 MPa, the bombardment angle was 90°, and the bombardment distance was 46 mm. After 4 min of bombardment, a 32 μm thick deformation layer was formed on the coating surface, of which 4.3×10 9 mm -2 High density of dislocations; (5) Precipitation of strengthening phase in wear-resistant and heat-resistant coating: The coating treated with supersonic particle bombardment was heated to 1000°C in vacuum, with an initial vacuum of 1Pa and a heating rate of 3°C / min. It was kept warm for 2 h to complete the solid solution, and then filled with argon for cooling; it was then heated to 830°C at a heating rate of 2°C / min. After keeping warm for 3 h, it was cooled in the furnace. A 0.3μm tetragonal topological σ phase was precipitated in the VCoNiMo in the wear-resistant and heat-resistant coating, and a 12nm L12 short-range ordered coherent nanophase was precipitated in the VCoNiMo phase in the deformation layer on the coating surface.
Claims
1. A multi-element wear-resistant and temperature-resistant protective coating material for a gas turbine, characterized in that Its composition is that the medium-entropy alloy powder containing Mo accounts for 20-30% by weight, and the rest is Cr3C2 powder; the molar ratio of Mo, Ni, Co and V in the medium-entropy alloy containing Mo is (1-2):10:10:10; the coating phase composition is Cr3C2+Ni+VCoNiMo with FCC structure + σ phase with tetragonal topological structure + α-MoO3 with orthorhombic structure, the coating thickness is 200-300μm, and its surface has a deformation layer with a thickness of 20-35μm, and a 5-15nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer.
2. A method for preparing a multi-element wear-resistant and temperature-resistant protective coating for a gas turbine, characterized in that The following steps are included in sequence: (1) Preparation of Mo-containing medium-entropy alloy powder: Mo, Ni, Co, and V powders were weighed in a molar ratio of (1-2):10:10:10, and the mixture was stirred and ball-milled for 72-120 h. After filtering and drying, a Mo-containing medium-entropy alloy powder with a particle size of 1.0-1.5 μm was prepared; (2) Preparation of multi-element wear-resistant and heat-resistant protective coating powder: Weigh the raw material powder according to weight percentage, of which the Mo-containing medium-entropy alloy powder accounts for 20-30%, and the rest is Cr3C2 powder; the weighed raw material powder is subjected to planetary ball milling for 10-15 hours, filtered and spray-dried, and then vacuum sintered at 1150-1250℃ for 1-2 hours to prepare the multi-element wear-resistant and heat-resistant protective coating powder; (3) Preparation of wear-resistant and heat-resistant coating by HVOF: The prepared protective coating powder is used as feed material, and the wear-resistant and heat-resistant coating is prepared by HVOF. During the thermal spraying process, part of the Mo element is oxidized to form α-MoO3 with a layered structure, and a σ phase rich in Mo and V is precipitated in the medium-entropy alloy matrix. The phase composition of the coating is Cr3C2+FCC structure VCoNiMo + tetragonal topological structure σ phase + orthorhombic structure α-MoO3 coating protective coating. The coating thickness is 200~300μm, and the size of the σ phase is about 0.5~0.8μm; (4) Surface treatment by supersonic particle bombardment: The protective coating surface was treated by supersonic particle bombardment using Al2O3 particles with an average particle size of 50 μm. The carrier gas was air with an air pressure of 1.0-1.5 MPa. After 2-5 min of bombardment, a 20-35 μm thick deformation layer was formed on the coating surface, of which 2×10 9 ~6×10 9 mm -2 High density of dislocations; (5) Precipitation of strengthening phase in wear-resistant and heat-resistant coating: The coating treated by supersonic particle bombardment is heated to 980~1100℃ in vacuum, kept at this temperature for 1~2h to complete solid solution, and then filled with argon for cooling; then heated to 800~850℃, kept at this temperature for 2~3h and then cooled in the furnace. A σ phase with a tetragonal topological structure of 0.1~0.3μm is precipitated in the VCoNiMo in the wear-resistant and heat-resistant coating, and a 5~15nm L12 short-range ordered coherent nanophase is precipitated in the VCoNiMo phase in the deformation layer on the coating surface.
3. The method for preparing the multi-element wear-resistant and temperature-resistant protective coating for a gas turbine according to claim 2, further characterized by: (1) When preparing the Mo-containing medium entropy alloy powder, the stirring ball milling speed is 700-800 r / min, WC-8Co grinding balls with a diameter of 6-10 mm are used, the ball milling medium is anhydrous ethanol, and the weight ratio of grinding balls: powder: anhydrous ethanol during ball milling is 30:2:
3. After ball milling, it is filtered with a 400-mesh screen and dried at 90-100°C. (2) When preparing the multi-element wear-resistant and heat-resistant protective coating powder, the ball mill speed is 300~400r / min, WC-10Co grinding balls with a diameter of 10mm are used, the ball milling medium is anhydrous ethanol, PEG4000 is added as a molding agent, and the weight ratio of grinding balls: powder: anhydrous ethanol: PEG2000 is 10:1:2:0.
26. After ball milling, a 400-mesh sieve is used for filtration. During spray drying, the atomizing disk speed is 6500~7000r / min, and the drying temperature is 120~130℃; (3) When HVOF is used to prepare wear-resistant and temperature-resistant coatings, the oxygen flow rate is 800~900L / min, the kerosene flow rate is 23~27L / h, the spray distance is 300~320mm, the powder feeding rate is 60~70g / min, and the spray gun moving speed is 800~1000mm / s; (4) When the supersonic particles bombard the surface for treatment, the bombardment angle is 90° and the bombardment distance is 40~50mm; (5) When the strengthening phase precipitates in the wear-resistant and heat-resistant coating, the initial vacuum degree is 0.5~1Pa and the heating rate is 1~5℃ / min.
Citation Information
Patent Citations
Hot spray anti-abrasion coating applicable to metal base materials and process for preparing hot spray anti-abrasion coating
CN109575650A
Wear-resistant protective composite coating and application thereof
CN117418229A